2014
DOI: 10.4103/0970-9290.135913
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience in high risk soft drinks factory workers of South India: A comparative study

Abstract: The caries experience was higher in workers working in soft-drinks factory and this study also showed that specific caries index can be used as a valid index for assessing dental caries experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…[ 3 ] From the dental perspective, the inherent acids and sugars in the soft drinks have both erosive and cariogenic potential. [ 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 ] From the dental perspective, the inherent acids and sugars in the soft drinks have both erosive and cariogenic potential. [ 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown direct relationship between dental caries and soft drinks. [ 4 5 10 11 12 13 ] Tooth erosion is progressive loss of tooth substance by acids that does not involve bacteria. The erosive potential of soft drinks depends on total titrable acids along with their pH.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown direct relationship between dental caries and soft drinks. [6,7] One nature product to increase caries prevention was tea. Many research focused on tea as herb that may reduce dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…They suffer from dental caries, periodontal disease, gingivitis, and tooth wear. 6 Consumption of carbonated beverages is considered as the risk factor for the gastroesophageal reflux disease (GERD) and regurgitation which leads to dental erosion. 7 Studies related to oral health of the soft drink factory workers are limited.…”
Section: Introductionmentioning
confidence: 99%